Light for the world to see - Alexander, Kwame (New York Houghton Mifflin Harcourt, 2020)
From NPR correspondent and New York Times bestselling author, Kwame Alexander, comes a powerful and provocative collection of poems that cut to the heart of the entrenched racism and oppression in America and eloquently explores ongoing events. A book in the tradition of James Baldwin$1 (Bs (3z(BA Report from Occupied Territory,(3y (BLight for the World to See is a rap session on race. A lyrical response to the struggles of Black lives in our world . . . to America$1 (Bs crisis of conscience . . . to the centuries of loss, endless resilience, and unstoppable hope. Includes an introduction by the author and a bold, graphically designed interior.s
Keywords: Poetry